INTERCROPPING SWEET POTATO WITH LEGUMES AS A CULTURAL MANAGEMENT SYSTEM - Quirol, Bernadette F.; Escalada , Rodolfo G.; Manatad, Fe A. (Annals of Tropical Research, 1984)
The use of legume intercrops reduced the overall growth of sweet potato. The yield of sweet potato declined by as much as 17.78% while that of the legumes by 14.94% due to competition for nutrients and light between the main crop and the intercrops. However, inoculation of the legume intercrops with Rhizobium minimized the competition for nitrogen and allowed the sweet potato to develop enough herbage. Sweet potato intercropped with inoculated legumes produced root yield which was 6.5% higher than that intercropped with uninoculated legumes. Significant differences were observed on the effects of legume intercrops and their interaction with inoculation on sweet potato productivity. Bushbean was a better intercrop than either mungbean or soybean because this legume matures earlier than the other two. Bushbean and mungbean increased sweet potato yield upon inoculation but inoculated soybean seemed to depress the yield of the root crop. In general, inoculation of the legume intercrops and intercropping were more beneficial and profitable. Intercropping was 4 and 3.5 times more profitable than monoculture when the legumes were inoculated and uninoculated, respectively.